In vitro Antioxidant and Antidiabetic Activities of the Bark Extracts of Kandelia candel (L.) Druce - Muhammed Habeebulla, M.; Velraj, Malarkodi (Asian Journal of Chemistry, 2022)
In present study, various extracts using different solvents such as petroleum ether, ethyl acetate and ethanol were subjected to in vitro antioxidant and antidiabetic activities. Ethanolic extract showed the highest activities in all antioxidant studies such as DPPH scavenging, ABTS scavenging and nitric oxide methods but it is comparatively weaker than standard drug ascorbic acid. In vitro antidiabetic activities were performed by using α-amylase and α-glucosidase inhibition in both method ethanolic extract showed highest activity, but the standard drug acarbose showed more potent than all other extracts. The highest antioxidant and antidiabetic activity of ethanolic extract may be due to the highest content phenols and flavanoids. Therefore, the ethanolic extracts contains potent antioxidant and antidiabetic compounds their isolation will help the invention of a new potent drug for the treatment diabetes and oxidative stress.